2023
DOI: 10.1101/2023.12.16.571680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hofbauer cells and fetal brain microglia share transcriptional profiles and responses to maternal diet-induced obesity

Rebecca Batorsky,
Alexis M. Ceasrine,
Lydia L. Shook
et al.

Abstract: SummaryMaternal immune activation is associated with adverse offspring neurodevelopmental outcomes, many mediated by in utero microglial programming. As microglia remain inaccessible throughout development, identification of noninvasive biomarkers reflecting fetal brain microglial programming could permit screening and intervention. We used lineage tracing to demonstrate the shared ontogeny between fetal brain macrophages (microglia) and fetal placental macrophages (Hofbauer cells) in a mouse model of maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…Excess maternal adiposity has been reported to alter the composition and function of maternal monocytes in peripheral blood, as well as macrophages found in placental and maternal adipose tissues during late gestation, toward a proinflammatory phenotype [ 33 , 47 ]. A recent study showed that Hofbauer cells and microglia share a similar developmental lineage and correlations in gene dysregulation were observed between the populations during maternal obesity [ 48 ]. This suggests that the readily abundant cells in the placenta provide insight into the developmental function of neonatal microglia.…”
Section: Impact Of Maternal Obesity/wsd On Maternal and Placental Imm...mentioning
confidence: 99%
“…Excess maternal adiposity has been reported to alter the composition and function of maternal monocytes in peripheral blood, as well as macrophages found in placental and maternal adipose tissues during late gestation, toward a proinflammatory phenotype [ 33 , 47 ]. A recent study showed that Hofbauer cells and microglia share a similar developmental lineage and correlations in gene dysregulation were observed between the populations during maternal obesity [ 48 ]. This suggests that the readily abundant cells in the placenta provide insight into the developmental function of neonatal microglia.…”
Section: Impact Of Maternal Obesity/wsd On Maternal and Placental Imm...mentioning
confidence: 99%